How Servant Leadership and Career Development Shape Employee Voice Behavior and Retention: The Mediating Role of Engagement and Moderating Effect of Gender - Ashfan, Mahadharu Ashifaati; Afrianty, Tri Wulida; Utami, Hamidah Nayati (Universitas Brawijaya, Indonesia, 2025)
In today's competitive and dynamic business environment, employee retention and engagement are critical challenges, particularly in organizations with a large millennial workforce. This study aims to analyze the effects of servant leadership and career development policy on employee engagement, employee voice behavior, and employee retention among millennial employees at PT. Petrokimia Gresik, while also examining gender as a moderating variable. Utilizing a quantitative approach, this explanatory study was conducted with a sample of 256 employees selected through purposive sampling. Data were collected from employees across various departments at PT. Petrokimia Gresik was analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The study employs the Stimulus-Organism-Response (S-O-R) theory as a theoretical framework to investigate the psychological and behavioral responses elicited by organizational stimuli, including leadership practices and career development policies. The results reveal that both servant leadership and structured career development policy significantly enhance employee engagement, promote employee voice behavior, and increase retention rates. It is found that gender does not significantly moderate the relationship between employee engagement and employee voice behavior; however, it plays a significant role in moderating the effect of employee voice behavior on retention. According to these results, organizations that prioritize employee-oriented leadership and provide clear career development opportunities foster a work environment supporting active participation and commitment. The practical implication of this study is that companies should integrate the principles of servant leadership and develop a systematic career development framework within their human resource strategies to cultivate a loyal and engaged workforce aligned with the organization's long-term goals.